Santri in the State: The Architecture of the NU Party Coalition at the End of the Soekarno Era 1952-1966 - Mahmud (Journal of Indonesian History, 2025)
This article examines the coalitional architecture of the Nahdlatul Ulama (NU) Party during 1952–1966 as a deliberate strategy to safeguard santri interests within the state, rather than a mere act of accommodation or resistance to the regime. Beginning with the 1952 Palembang Congress—when NU withdrew from Masyumi and established its own political party—this study maps two axes of coalition: the horizontal (cross-party and cross-ideological alliances, from the 1950s cabinets to limited accommodation within the Nasakom scheme) and the vertical (the governance of the Syuriah–Tanfidziyah structure and autonomous bodies that mediated between syar‘iyyah rationality and siyasiyyah calculation). Employing a historical–qualitative approach (heuristics, source criticism, interpretation, historiography) complemented by light quantitative mapping (coalition timelines, cabinet participation frequency, distribution of political offices), the data are drawn from congress proceedings, organizational decrees, elite speeches and memoirs, contemporary press archives, and selected interviews. The key findings reveal that (1) religious legitimacy grounded in fiqh siyasah and the doctrine of waliyyul amri ad-daruri bisy-syaukah served as the normative foundation of NU’s coalition; (2) the strategic use of executive–legislative positions—especially the Ministry of Religious Affairs—converted pesantren cultural authority into policy leverage; and (3) internal correction mechanisms between senior ulama and younger elites functioned as an ideological safeguard, particularly amid rising tensions with the PKI before and after 1965. The study’s contribution lies in conceptualizing a model of “coalitional architecture” that integrates structure–process–discourse as an analytical lens to interpret the Islam–state relationship at the end of the Sukarno era, and to explain why NU’s political choices appeared ambivalent yet consistently aimed to preserve policy access while minimizing political costs for the pesantren base.